Implementasi PSAK No. 109 Pada Organisasi Pengelolaan Zakat dan Perannya dalam Meningkatkan Akuntanbilitas dan Transparansi Pada Baitul Mal Provinsi Aceh - Safrirullah; Hafas Furqani; Nilam Sari (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This research aims to find out and analyze the implementation of PSAK No. 109 Concerning Zakat, Infaq and Sadaqah on Zakat Management Organizations (OPZ) in Increasing Accountability and Transparency in Baitul Mal Aceh Province. In this research, the methodology used is: descriptive research with a qualitative approach. The results of this research show that: (1) Baitul Mal Aceh (BMA) Aceh Province has implemented PSAK No. 109 in terms of Financial Reporting including the Aspects of Recognition, Measurement, Presentation and Disclosure of Zakat funds, Infaq/Alms and other Religious Assets (HKL) which is in accordance with the Standardization and provisions in the Statement of Financial Accounting Standards No. 109 concerning Zakat, Infaq and Alms. In terms of accountability, Baitul Mal Aceh has fulfilled the aspects of accountability and transparency as a public service in carrying out the process of auditing its financial reports every period and conveying information openly through information media (print, digital and website) regarding financial reports as a form of responsibility/accountability and transparency to the Community (Mustahik and Muzakki) and obtaining the WTP (Fair Without Exception) Predicate from the Aceh Government. (2) In the process of implementing Statement of Financial Accounting Standards No. 109 concerning Zakat, Infaq and Alms Accounting, Baitul Mal Aceh (BMA) has several obstacles or obstacles in implementing PSAK No. 109 Standardization, in the form of a lack of competent Human Resources (HR). in the field of financial accounting and the absence of a system or application/program in preparing financial reports for Zakat, Infaq and Alms.